Innovation, R&D Investment and Productivity: Uruguayan Manufacturing Firms - Adriana Cassoni; Magdalena Ramada (Inter-American Development Bank (IDB), 2010)
Uruguays inability to sustain high levels of economic growth cannot be fully explained by external shocks, the prevailing institutional setting or the level of human capital accumulation. Instead, low investment in knowledge capital stands as a most likely explanation. This hypothesis is supported by empirical evidence analyzed in this study. Returns on innovation were found to be significant, promoting a non-negligible acceleration of labor productivity gains. However, the propensity to innovate and the intensity of the effort expended critically depend on the firms already having a high internal efficiency level. As firms behavior is differentiated depending on the type of innovation output pursued, the significantly higher frequency of processes relative to product-innovative firms is matched by the larger impact of novel processes with respect to products on labor productivity. However, the degree of novelty of process innovation is significantly inferior to that of product innovation. The research points to inadequate choices of input mixes as the underlying cause. Policy recommendations center on finding adequate channels to generate and disseminate information on the optimal input mixes depending on the type of innovation output sought.
Keywords: O31; O32; D21; 330; Innovation input; Innovation output; Productivity growth; CDM model